Lung donation after circulatory determined death: a single-centre experience. (1st August 2018) - Barbero, Cristina; Messer, Simon; Ali, Ayyaz; Jenkins, David P; Dunning, John; Tsui, Steven; Parmar, Jasvir
Abstract: OBJECTIVES: Donor organ utilization and shortage remain the major limitations to the opportunity of a lung transplantation (LTx). Donation after circulatory determined death (DCD) has been adopted as a source of additional organs worldwide. However, concerns about organ quality and ischaemia–reperfusion injury have limited its application. The aim of this study was to retrospectively analyse a single-centre experience in the DCD LTx and compare early and mid-term outcomes with those from a standard donation after brain death (DBD). METHODS: During the 6-year study period, 186 LTxs were performed: 147 bilateral LTxs (79%) and 39 single LTxs (21%). Of these, 23 recipients received organs retrieved from DCD donors (12.4%). RESULTS: No differences were found between the 2 groups of recipients except for age and cystic fibrosis as an underlying disease. No differences in terms of duration of mechanical ventilation, incidence of postoperative extracorporeal membrane oxygenation support, intensive care unit stay, hospital length of stay, airway anastomotic complications, incidence and grade of rejection and freedom from bronchiolitis obliterans syndrome were demonstrated. There was a non-statistically significant trend towards older age in the DCD group. Actuarial survival in the subgroup of bilateral LTx at 1 year and 5 years was 75% and 51% for the DCD group and 82% and 61% for the DBD group, respectively ( P = 0.12). CONCLUSIONS: Short- and medium-term outcomes after the DCD LTx are comparable with those achieved after transplantation from the DBD donors, despite a tendency to use DCD lungs for older recipients. Therefore, the DCD LTx is a clinical option that can be used with favourable results to expand the lung donor pool.